Investigation of Valence Mixing in Sodium-Ion Battery Cathode Material Prussian White by Mössbauer Spectroscopy - Ericsson, Tore; Häggström, Lennart; Ojwang, Dickson O.; Brant, William R. (Frontiers in Energy Research, 2022)
Prussian white (PW), Na2Fe [Fe(CN)6], is a highly attractive cathode material for sustainable sodium-ion batteries due to its high theoretical capacity of ∼170 mAhg−1 and low-cost synthesis. However, there exists significant variability in the reported electrochemical performance. This variability originates from compositional flexibility possible for all Prussian blue analogs (PBAs) and is exasperated by the difficulty of accurately quantifying the specific composition of PW. This work presents a means of accurately quantifying the vacancy content, valence distribution, and, consequently, the overall composition of PW via Mössbauer spectroscopy. PW cathode material with three different sodium contents was investigated at 295 and 90 K. The observation of only two iron environments for the fully sodiated compound indicated the absence of [Fe(CN)6]4- vacancies. Due to intervalence charge transfer between iron centers at 295 K, accurate determination of valences was not possible. However, by observing the trend of spectral intensities and center shift for the nitrogen-bound and carbon-bound iron, respectively, at 90 K, valence mixing between the iron sites could be quantified. By accounting for valence mixing, the sum of iron valences agreed with the sodium content determined from elemental analysis. Without an agreement between the total valence sum and the determined composition, there exists uncertainty around the accuracy of the elemental analysis and vacancy content determination. Thus, this study offers one more stepping stone toward a more rigorous characterization of composition in PW, which will enable further optimization of properties for battery applications. More broadly, the approach is valuable for characterizing iron-based PBAs in applications where precise composition, valence determination, and control are desired.